Research on the Historical Dynamics of Baicheng Oil Chicken Populations - Huie Wang; Tianci Liu; Gang Wang; Xiurong Zhao; Chengqian Wang; Fugui Li; Gemingguli Muhatai; Lujiang Qu (Animals)
This study is based on the whole gene resequencing data of 162 individuals from 16 chicken breeds. We calculated the historical effective population size (Ne), differentiation time and genetic hybridization degree of the population to understand its historical dynamics, in order to provide a theoretical basis for the scientific protection and utilization of the germplasm resources of Baicheng Oil Chicken (BCY). The main results are as follows: using SMC++ and fastsimcoal2 software, respectively, we estimated Ne of BCY at 46,066 in the past and inferred a divergence time of 428–548 years ago. D-statistical analysis revealed a ~7% genetic introgression from White Leghorn chicken (LH) to BCY. Notably, infiltration genes such as CTNNAL1 (potentially influencing egg production) and RARX (possibly associated with fat deposition) were identified. These findings provide insights into BCY’s demographic history and support its genetic conservation and utilization.